Design and Fabrication of an Arduino-Based 5-DoF Robotic Arm for Pick-and-Place Applications - AMAKOROMO, T. E.; OKOYE, O. E. (European Journal of Science, Innovation and Technology, 2026)
The design, construction, control, and performance assessment of an Arduino-based, five-degree-of-freedom robotic arm intended for pick-and-place tasks are presented in this work. Using acrylic structural elements, six AD002 servo motors, an Arduino UNO R3 microcontroller, an Adept driver board, and Bluetooth-based control via an Android interface, the prototype was created as an inexpensive educational and testing platform. With consideration for payload capacity, structural stability, and convenience of use, the system was set up to offer synchronised motion at the base, shoulder, elbow, wrist, and gripper joints. Following assembly and calibration, three objects weighing 0.0245 kg, 0.0297 kg, and 0.0347 kg were used to test the robotic arm over a predetermined distance of 0.061 m. Higher payloads required more actuator effort and longer completion times, but the arm successfully finished all pick-and-place trials. The outcomes demonstrated that the system maintained adequate stability and repeatability during testing and operated dependably under modest loads. In addition to pointing up possibilities for future development in cargo handling, structural strengthening, and motion efficiency, the study shows that a basic microcontroller-based robotic arm can function as an efficient model for robotics education, embedded control, and small-scale automation.